Analysis of The Physical Condition Test Results of East Java Cricket PON BK Athletes - Djalu Pratama; Imam Hariadi (STKIP Paasundan Press, 2025)
This study aims to analyze the physical condition of cricket athletes from East Java who participated in the PON Qualification Round, based on eight components of physical fitness. The research employed a descriptive quantitative approach involving 31 athletes (16 male and 15 female), measuring eight key physical fitness components: abdominal muscle strength, leg power, upper arm strength, lower back strength, upper arm endurance, abdominal endurance, flexibility, and cardiorespiratory endurance. The results showed that male athletes demonstrated good lower back strength and abdominal endurance (60%), but had weaknesses in speed and upper arm strength (70% fell into the moderate–poor category). Female athletes exhibited widespread deficiencies, particularly in the chin-up and single-leg squat tests, with 80% scoring in the low category. These suboptimal physical conditions significantly affect technical performance in cricket, including throwing, sprinting, and fielding, which demand strength, speed, and endurance. The findings suggest the need for a more targeted and specific physical training program to support the technical performance of athletes during competition